Structure-activity studies: In vitro antileishmanial and antimalarial activities of anthraquinones from morinda lucida. - Sittie, A.A.; Lemmich, E.; Olsen, C.E.; Hviid, L.; Kharazmi, A.; Nkrumah, F.K.; Christensen, S.B. (Planta Medica, 1999)
Anthraquinones have been isolated by bioassay guided fractionation from Morinda lucida. Structure-activity studies show that an aldehyde group at C-2 and a phenolic hydroxy group at C-3 enhance the activity of the anthraquinones against the growth of Plastnodium falciparum and promastigotes of Leishmania major in vitro.